Hypoxylon luteogranulatum (Hypoxylaceae, Xylariales), a novel species from Thailand with distinct chemical and ecological traits - Sarunyou Wongkanoun; Esteban Charria-Girón; Marjorie Cedeño-Sanchez; Boonchuai Chainuwong; Sayanh Somrithipol; Eric Kuhnert; Prasert Srikitikulchai; Natapol Pornputtapong; Frank Surup; Jennifer Luangsa-ard; Marc Stadler (Mycology)
During the course of our ongoing study of the diversity of Thai fungi and their secondary metabolites, numerous specimens within the Hypoxylaceae have been characterised by traditional morphology, chemotaxonomy using ultra-high-performance liquid chromatography coupled to diode array detection and ion mobility tandem mass spectrometry (UHPLC-DAD-IM-MS/MS), and molecular phylogenetic analyses. MS/MS-based analysis of the major stromatal metabolites of a newly identified taxon, Hypoxylon luteogranulatum, indicated the production of distinct compounds compared to the azaphilone and binaphthalene pigments commonly found in the Hypoxylaceae, aside from the presence of the chemotaxonomic marker binaphthalene tetrol (BNT). Further analysis suggested that one of the major metabolites had the molecular formula C13H13NO3, identical to hypoxyvermelhotin A, a yellow pigment so far exclusively found in Hypoxylon lechatii. Its identity was confirmed after purification by preparative high-performance liquid chromatography with nuclear magnetic resonance (NMR) data, and genome analysis of H. lechatii revealed the presence of different hybrid polyketide synthases-non-ribosomal peptide synthetases (PKS-NRPS) hybrid clusters. Despite chemotaxonomic similarities with H. lechatii, we propose a new species, which is morphologically distinct from H. lechatii. Our molecular phylogenetic study provides substantial evidence distinguishing H. luteogranulatum clearly from H. lechatii and allied members within the Hypoxylaceae. Additionally, future studies are needed to better understand the ecological behaviour of H. luteogranulatum and identify the ecological role of the vermelhotin-like molecules within this putative interaction.